(untitled) (European Journal of Language and Literature, 2019)
Many studies have described the use of mobile assisted language learning in language teaching and learning; yet, the number of studies in listening skill remains unsatisfactory. Few researchers appear to have considered how to use mobile learning devices to support pedagogical approach to develop academic listening skills. Several studies in the past, required learners to read from mobile phones rather than listening to audios. There were attempts to use computer technology integration into instruction; however, few were in mobile technology. The interest in research related to the impact of mobile assisted language learning on developing students’ listening skills remains relatively low and consequently listening has been neglected. Thus, the current paper aims at exploring the effectiveness of mobile assisted language learning devices both as instructional tools and learning resources within and beyond classroom learning environments to develop language skills in particular listening sub-skills. The experimental design is pretest-experiment-post-test. To conduct the study two groups of experimental (30) and control (30) out of 60 second year students at Al Iraqia University/ college of education for women/ department of English were made. Both groups were taught the same material, but using different methods. The results of the post-test indicated that the use of mobile assisted language learning devices had impacts on developing experimental group’s listening skills and outperformed the control group.